Digital Divide Against Development E-Government In The District Sinjai - Muhammad Takdir; Sukarno Hatta; Dedi Ariyadi; Muhammad Lutfi (Universitas Negeri Makassar, 2021)
The digital divide or Digital Divide is an economic gap related to the access, use, or impact of information and communication technology. E-government is a form of implementing the use of information technology for government services to the public. E-government development is an effort to organize an electronic-based government system in order to improve the quality of public services effectively and efficiently. This research is a qualitative research which is a holistic single-case study with research locations in the District and District of Sinjai. The data collection technique used in this research is semi-structured interview. The sampling technique in this study used purposive sampling. The informants of this research were represented from the government, the private sector/ICT entrepreneurs, communities/ICT practitioners and some from the general public. Data analysis techniques used are data collection, data reduction (data reduction), data presentation (data display), and conclusions. The results of the research carried out can be concluded that the provision of access to information for ASN within the government of Sinjai Regency is quite good and easy, while the availability of technology for them to be able to take advantage of it does take time, especially in the conditions of our region, it is not easy, all people can access information from the government with a technology. data reduction (data reduction), data presentation (data display), and conclusions. The results of the research carried out can be concluded that the provision of access to information for ASN within the government of Sinjai Regency is quite good and easy, while the availability of technology for them to be able to take advantage of it does take time, especially in the conditions of our region, it is not easy, all people can access information from the government with a technology. data reduction (data reduction), data presentation (data display), and conclusions. The results of the research carried out can be concluded that the provision of access to information for ASN within the government of Sinjai Regency is quite good and easy, while the availability of technology for them to be able to take advantage of it does take time, especially in the conditions of our region, it is not easy, all people can access information from the government with a technology.